INTERPRETATION OF THE CONCEPT IN ONTOLOGY AND THESAURUS - Kadirova Zebo Gulboyevna (Western European Studies, 2025)
Today, a number of researches are being conducted in Uzbek linguistics on computer linguistics, including machine translation, corpus technology, computer lexicography, and the development of linguistic foundations of software applications, processing of lexicographic texts, and linguostatistical analysis, to a certain extent. With the increase in the flow of information, there is a need to search for new methods of its storage, presentation, formalization, and systematization, as well as automatic processing. Ontology is notable for being the basis for the implementation of a search system based on semantic relationships between information. This article classifies ontological models and analyzes the components of the thesaurus model. In addition, the differences in the concept of a concept in ontology and thesaurus are studied. While the thesaurus organizes terms based on synonyms, hierarchical relationships, and associative links, ontology provides a semantic basis for concepts, defining their properties.
Keywords: ontology; thesaurus; ontological knowledge model; thesaurus knowledge model